The coherence of EU law - Prechal, Sacha (Oxford University Press, 2008)
Believers in common concepts argue that there is a relatively clear, shared and accepted framework of ideas, providing an understanding of the system that is ultimately unified in spite of all apparent divergence. Sceptics hold that there is no such framework; 'common concepts' turn out to be additional sources of misunderstanding, confusion and, subsequently, legal divergence. According to a third thesis, there is indeed no common conceptual core, but the necessary unity and coherence of EU law can be articulated and even reinforced through the use of divergent concepts